The Integration of Artificial Intelligence in Drug Discovery and Development : Novel Approach (International Journal of Scientific Research in Science and Technology, 2024)
The drug discovery and development process is complex, time-consuming, and costly. Artificial Intelligence (AI) has emerged as a transformative technology to improve efficiency, accuracy, and innovation in pharmaceutical research. This study explores the applications, benefits, and challenges of integrating AI in drug discovery and development. the role of AI in drug discovery, its transformative impact on pharmaceutical research, and the potential benefits and challenges. Briefly mention the major AI techniques used in different phases of drug discovery and development. The integration of Artificial Intelligence (AI) into drug discovery and development is transforming the pharmaceutical industry by speeding up processes, reducing costs, and enhancing precision. This paper discusses the involvement of AI in drug discovery and development. AI has brought a revolution to drug invention and development, significantly reducing costs and accelerating the process. By integrating AI into these stages, drug development has become more efficient, allowing for faster and more cost-effective innovations in the pharmaceutical field.